Yiddish Paris : Staging Nation and Community in Interwar France - Underwood, Nick, 1977- (Book collections on Project MUSE., 2022)
"Yiddish Paris explores how Yiddish-speaking emigrants from Eastern Europe in Paris in the 1920s and 1930s created a Yiddish diaspora nation in Western Europe and how they presented that nation to themselves and to others in France. In this meticulously researched and first full-length study of interwar Yiddish culture in France, author Nicholas Underwood argues that the emergence of a Yiddish Paris was depended on "culture makers," mostly left-wing Jews from Socialist and Communist backgrounds who created cultural and scholarly organizations and institutions, including the French branch of YIVO (a research institution focused on East European Jews), theater troupes, choruses, and a pavilion at the Paris World's Fair of 1937. Yiddish Paris examines how these left-wing Yiddish-speaking Jews insisted that even in France, a country known for demanding the assimilation of immigrant and minority groups, they could remain a distinct group, part of a transnational Yiddish-speaking Jewish nation. Yet, in the process, they in fact created a French-inflected version of Jewish diaspora nationalism, finding allies among French intellectuals, largely on the left"--